Multilingual SEIR public opinion propagation model with social enhancement mechanism and cross transmission mechanisms - Suyalatu Dong; Linlin Xu; Zhong-Zhou Lan; Yana A; Fanyu Bu; Wu Hua; Qu Chunlai; Li Yifei; Gao Minjie; Ge Kai (Scientific Reports)
Abstract The propagation of public opinion in multilingual environments presents unique challenges due to the diversity of languages, cultures, and values. This study develops an SEIR-based model tailored for multilingual contexts, incorporating mechanisms such as social enhancement, forgetting, and cross-transmission. The model’s purpose is to improve transparency, inclusivity, and effectiveness in public opinion management, particularly in diverse linguistic settings. By emphasizing democratic engagement and avoiding social control, the model provides tools for managing public opinion that promote fairness and transparency. The model was validated using real Twitter data related to COVID-19 across multiple languages, including English, Spanish, and Catalan. Key results demonstrate that the model effectively captures the dynamics of opinion propagation, particularly in languages with fewer users, where opinion spread tends to be more predictable. By addressing cultural and linguistic differences, this study offers an inclusive approach to public opinion management. The inclusivity ensures that different cultural groups, regardless of language, are fairly represented in public discourse. This research contributes to the ethical management of public opinion, providing valuable insights for policymakers and analysts in multilingual societies.